The Concept of Habituation Learning in Developing Students' Talents, Interests, and Creativity in Dance Art Learning at Andhe-andhe Lumut Art Studio Kediri - Setyowati, Putri Jania; Muhajir, Muhajir; Wahyuningtyas, Sri (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The background of this research was that education in contemporary Indonesia used to emphasize academic abilities. Society used to consider the acquisition of grades in a subject and use it as a measure of success in learning. Additionally, the preservation of cultural heritage and the fundamental cultural data statistics in East Java used to be uneven. This research aimed to: 1) Analyze the concept of habituation learning; 2) Analyze the implementation of the habituation concept in developing talents, interests, and creativity. This research used a qualitative method by observing events that occurred in the field, noting what happened, analyzing documents found in the field, creating transcripts of field findings, and generating a detailed research report. The research was conducted at Andhe-andhe Lumut Art Studio Kediri, observing all the learning activities. Data sources for this research were informants, including studio trainers, studio owners, studio users, and studio students; places and events; relevant studio-related documents. Data were collected through observation, interviews, and documentation. The research resulted the following findings: 1) The concept of habituation was carried out in six stages: thinking, recording, repetition, storage, repetition again, habit; 2) Talent was supported by factors like navitis, empirical, convergence; 3) Interest was affected by factors like attention, pleasure, willingness; 4) Creativity was executed in four stages: preparation, incubation, illumination, confirmation, which encompassed the ability to create dance floor patterns, create movements, and produce new dance works